2019
DOI: 10.1002/biof.1545
|View full text |Cite
|
Sign up to set email alerts
|

Antimetastatic effects of calycosin on osteosarcoma and the underlying mechanism

Abstract: Osteosarcoma (OS) refers to a malignant tumor with potential invasiveness and metastasis; however, the current chemotherapy of OS is lacking. Thus, the alternative drug for treating OS is urgent to explore. Calycosin (CC) is evidenced in our previous study to play the anti‐OS benefits for suppressing cancer cell proliferation. Consequently, further investigation of CC‐medicated anti‐invasive and metastatic effects against OS is needed. In the current study, the clinical samples of OS patients were collected fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…And the downregulation of ECT2 by siRNA and miR-223 could suppress osteosarcoma cell migration and invasion [58,59] . Moreover, Qiu et al [60] . found that Calycosin could inhibit osteosarcoma cell migration through restraining metastasis-associated IκBα/ECT2 signal pathway, but further research is needed to con rm the results.…”
Section: Discussionmentioning
confidence: 99%
“…And the downregulation of ECT2 by siRNA and miR-223 could suppress osteosarcoma cell migration and invasion [58,59] . Moreover, Qiu et al [60] . found that Calycosin could inhibit osteosarcoma cell migration through restraining metastasis-associated IκBα/ECT2 signal pathway, but further research is needed to con rm the results.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have extensively reported the anticancer and antimetastatic activities of calycosin in various types of cancer, including breast cancer, colorectal cancer, ovarian cancer and nasopharyngeal carcinoma ( 10 , 11 , 15 ). It was also reported that calycosin exerted an inhibitory effect on the growth of osteosarcoma ( 9 ). Sun et al ( 12 ) observed that calycosin induced apoptosis of estrogen receptor + MG-63 osteosarcoma cells via the PI3K/Akt/mTOR pathway.…”
Section: Discussionmentioning
confidence: 95%
“…Mitochondrial dependence signaling occurs through cleavage of caspase-9, which then activates downstream caspase-3, leading to cleavage of key cell substrates, including PARP, thereby inducing apoptosis ( 22 ). It was previously reported that calycosin exerts an anti-osteosarcoma effect, and its mechanism was associated with the activation of apoptosis ( 9 ). The present study also demonstrated that treatment with calycosin led to the cleavage of caspase-3, caspase-9 and PARP in osteosarcoma 143B cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The degradation of ECM by MMPs is a key step in the invasion and metastasis processes in human cancers, and increased secretion and activity of MMPs are implicated in numerous types of malignant tumours ( 22 , 23 ). MMP2 and MMP9 are important members of the MMP family and inhibition of their expression is a strategy for reducing the invasion and metastasis of osteosarcoma ( 24 , 25 ). The current western blot analysis showed that enoxacin treatment downregulated the expression of MMP2 and MMP9 in 143B cells, which could be an effective way to inhibit osteosarcoma metastasis.…”
Section: Discussionmentioning
confidence: 99%